Community matrons: primary care professionals' views and experiences. - Chapman, L; Smith, A; Williams, V; Oliver, D (2009)
AIM: This article is a report of a study exploring how the role of the community matron is progressing and any barriers or facilitators to performing the role. BACKGROUND: Long-term conditions are distressing for patients and costly for healthcare services. Government policy in western countries has increasingly focussed on more integrated and pro-active management of patients with multiple long-term conditions to maintain the ability of the aging population to function independently. The role of community matrons has been introduced in England in an attempt to address these issues. METHOD: A purposive sample of 31 health and social care professionals participated in five focus group discussions. Reported experiences of the community matron role by community matrons, district nurses, social workers and general practitioners were analysed according to the principles of grounded theory. Data were collected in 2007. FINDINGS: The community matron role was seen as effective in meeting the medical and social needs of patients. This was achieved through patient education, developing patients' self-management of their health conditions and monitoring their social needs. Potential barriers to success of the role were associated with lack of role definition prior to its introduction. CONCLUSION: It is unclear whether the role is financially viable in its current form. Further research is required to examine differing models for implementing the role and judging its effectiveness in bridging the primary-secondary care interface.